In vitroactivity of colistin in antimicrobial combination against carbapenem‐resistantAcinetobacter baumanniiisolated from patients with ventilator‐associated pneumonia in Vietnam. Issue 10 (October 2015) - Le Minh, Vien; Thi Khanh Nhu, Nguyen; Phat, Voong Vinh; Thompson, Corinne; Huong Lan, Nguyen Phu; Thieu Nga, Tran Vu; Thanh Tam, Pham Thi; Tuyen, Ha Thanh; Hoang Nhu, Tran Do; Van Hao, Nguyen; Thi Loan, Huynh; Yen, Lam Minh; et al.
Abstract : N/A: Acinetobacter baumannii has become one of the major infection threats in intensive care units (ICUs) globally. Since 2008, A. baumannii has been the leading cause of ventilator‐associated pneumonia (VAP) in our ICU at an infectious disease hospital in southern Vietnam. The emergence of this pathogen in our setting is consistent with the persistence of a specific clone exhibiting resistance to carbapenems. Antimicrobial combinations may be a strategy to treat infections caused by these carbapenem‐resistant A. baumannii . Therefore, we assessed potential antimicrobial combinations against local carbapenem‐resistant A. baumannii by measuring in vitro interactions of colistin with four antimicrobials that are locally certified for treating VAP. We first performed antimicrobial susceptibility testing and multilocus variable number tandem repeat analysis (MLVA) genotyping on 74 A. baumannii isolated from quantitative tracheal aspirates from patients with VAP over an 18‐month period. These 74 isolates could be subdivided into 21 main clusters by MLVA and >80 % were resistant to carbapenems. We selected 56 representative isolates for in vitro combination synergy testing. Synergy was observed in four (7 %), seven (13 %), 20 (36 %) and 38 (68 %) isolates with combinations of colistin with ceftazidime, ceftriaxone, imipenem and meropenem, respectively. Notably, more carbapenem‐resistant A. baumannii isolates (36/43; 84 %) exhibited synergistic activity with a combination of colistin and meropenem than carbapenem‐susceptible A. baumannii isolates (2/13; 15 %) ( P = 0.023; Fisher's exact test). Our findings suggest that combinations of colistin and meropenem should be considered when treating carbapenem‐resistant A. baumannii infections in Vietnam, and we advocate clinical trials investigating combination therapy for VAP.